Keanekaragaman Serangga Asosiatif pada Bangkai Tikus yang Diletakkan di Luar Ruangan sebagai Indikator Forensik - Aini, Aprilia Nurul; Rahadian, Rully; Khotimah, Khusnul (Biocaster : Jurnal Kajian Biologi, 2025)
Insects are a group of organisms with a high level of species diversity and have various important roles, one of which is in the field of forensics. Insects can be used as forensic indicators in revealing the facts of death studied in forensic entomology. This study aims to analyze the diversity of insects associated with rat (Rattus norvegicus) carcasses in three different conditions, namely without treatment (control), wrapped in cloth, and with incisions. This study used a Randomized Block Design (RBD) with three replications for each treatment. The treatment group consisted of three types, namely without treatment, with cloth wrapping, and with incisions. Each group consisted of three replications. The results of the Hutcheson t-test showed differences in the insect species diversity index between treatments (p < 0.05). The species Onthophagus pilularius and Phaeochrous emarginatus were only found in carcasses wrapped in cloth. Meanwhile, Chrysomya megacephala was the dominant species in all treatments with a relative abundance of more than 40%. These findings indicate that the physical condition of the carcass influences the composition of the insect community, which has the potential to be used as an indicator in forensic studies.